Musiqa o‘qituvchisi har tomonlama kompetentlik talablari (SCIENCE and SOCIETY, 2023)
The content of the article concerns the requirements for increasing the comprehensive competence of music education teachers and students, as well as future music teachers, in developing students‘ ability to listen to music through the processes of musical competence, musical taste, and moral qualities. aesthetic views, it is written about the process of combining several competencies in the formation of musical-theoretical, musical-historical knowledge, a broad